Annealing effects on the microstructural properties of the ZnO thin films grown on p-InP (100) substrates - Yuk, J. A.; Son, D. I.; Kim, T. W.; Kim, J. Y.; Choi, W. K. (KOREAN PHYSICAL SOC, 2008)
The effects of thermal annealing on the microstructural properties of ZnO thin films grown on p-InP (100) substrates were investigated by using X-ray diffraction (XRD), atomic force microscopy (AFM), transmission electron microscopy (TEM), selected-area electron diffraction (SAED) and electron energy loss spectroscopy (EELS) measurements. XRD, AFM, TEM, SAED and EELS results showed that ZnO amorphous layers were formed in the top and the bottom regions of the ZnO thin films due to the thermal treatment. The formation of the ZnO amorphous layer in the ZnO thin film annealed at 600 degrees C was attributed to the accumulation of Zu vacancy layers. The formation of an amorphous layer in the top surface of the ZnO film improved the surface morphology of the ZnO film. The c-axis orientation of the ZnO films became more preferential with increasing annealing temperature.
Keywords: OPTICAL-PROPERTIES; LASERS; LAYER